Co‐doping effects of (Al, Ti, Mg) on the microstructure and electrical behavior of ZnO‐based ceramics. Issue 5 (21st January 2020) - Sun, Qianying; Li, Guorong; Tian, Tian; Zeng, Jiangtao; Zhao, Kunyu; Zheng, Liaoying; Barré, Maud; Dittmer, Jens; Gouttenoire, Francois; Rousseau, Anthony; Kassiba, Abdel Hadi
Abstract: Co‐doped ZnO‐based ceramics using Al, Ti, and Mg ions in different ratios were synthesized with the objective to investigate the doping effects on the crystalline features, microstructure and the electrical behavior. For Al and Ti doping, a coexistence of crystalline phases was shown with a major wurtzite ZnO structure and secondary spinel phases (ZnAl2 O4, Zn2 TiO4, or Zna Tib Alc Od ), while Mg doping did not alter significantly the structural features of the wurtzite ZnO phase. The electrical behavior induced by Al, Ti, and Mg co‐doping in different ratios was investigated using Raman, electron paramagnetic resonance (EPR) and 27 Al and 67 Zn solid‐state nuclear magnetic resonance (NMR). Al doping induces a high electrical conductivity compared to other doping elements. In particular, shallow donors from Zni ‐AlZn defect structures are inferred from the characteristic NMR signal at about 185 ppm; that is, quite far from the usual oxygen coordinated Al. The Knight shift effect emanating from a highly conducting Al‐doped ZnO ceramics was considered as the origin of this observation. Oppositely, as Ti doping leads to the formation of secondary spinel phases, EPR analysis shows a high concentration of Ti 3+ ions which limit the electrical conductivity. The correlation between the structural features at the local order, the involved defects and the electrical behavior as function of the doping process are discussed.